Epidemiological investigation of a food poisoning outbreak: a study among hostel dwelling students and resident doctors of a tertiary healthcare facility of India - Singh, Chandramani; Biswas, Bijit; KG, Naveen; Hari, Haripriya; Pandey, Sanjay; Naik, Bijaya Nanda (Indian Journal of Community Health, 2021)
Background: During second week of February, 2021 several cases of food poisoning were reported from hostels of a tertiary healthcare facility, thus this epidemiological investigation was undertaken, to confirm existence of a food poisoning outbreak, describe cases as per person, place, time and predominant food source, identify the attributes associated with the outbreak. Methods: To investigate the suspected food poisoning outbreak, an online unmatched case control study was conducted among 440 hostel dwelling students and resident doctors of a tertiary healthcare facility of eastern India during February, 2021. Results: The proportion of the study subjects who reported to have experienced food poisoning symptoms was 23.9%. Most of the food poisoning event reported to have occurred during 10th February, 2021 (26.6%). In the multivariable logistic regression model, predominant consumption of food from girls’ hostel mess [adjusted odds ratio (AOR): 7.83 (1.58-38.79)] and canteen 1 [AOR: 4.83 (1.13-20.69)] were found to be multivariable predictors of food poisoning events adjusted with age, gender, designation and residing hostel. Conclusion: One in every four study participants opined to have experienced food poisoning symptoms during the study period. This confirmed the existence of a multi-source food poisoning outbreak in the study population.